Pemanfaatan ekstrak protein dari kacang-kacangan sebagai koagulan alami: review - Hans Kristianto; Susiana Prasetyo; Asaf Kleopas Sugih (Jurnal Rekayasa Proses, 2019)
Coagulation and flocculation are commonly used in water and wastewater treatment. Inorganic coagulant such as alum (Al2(SO4)3), ferrous sulphate (FeSO4), and polyaluminium chloride (PAC) are commonly used. These coagulants are known for its effectiveness and simple operation procedure. However, there are some drawbacks such as reduction in pH, potential negative health effect when the treated water is consumed, and large sludge volume. To overcome these problems, utilization of natural coagulants has been proposed. Based on its active coagulating agent, natural coagulant could be divided as polyphenolic, polysaccharides, and protein. Protein from beans and seeds is commonly used as the source of active coagulating agent, due to its effectiveness, availability, and relatively simple pretreatment is needed. Usually the protein is extracted by using 0.5-1 M NaCl solution as globulin is the major protein fraction in beans.The extracted protein could act as cationic polymer to neutralize negatively charged colloids through adsorption-charge neutralization mechanism. Extracted protein could work effectively to treat turbid and waste water with lower cost compared to alum. However, most of existing studies are still focused on small – pilot scale utilization thus further explorations are still needed.